THE IMPACT OF REWARD AND PUNISHMENT MECHANISMS ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF WORK MOTIVATION - Azzahra, Ghevira; Barry, Rinto Rain (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to explore the impact of rewards and punishments on employee performance, with an emphasis on the mediating role of work motivation in companies operating in the food industry. Data were collected through a questionnaire distributed to 96 employees of the company, and the analysis was conducted using PLS-SEM via the WarpPLS 7.0 application. The results indicate that rewards have a significant impact on work motivation and employee performance, while constructively applied punishments also positively affect performance, although their effect is smaller compared to that of rewards. Work motivation has been shown to act as a significant mediator in the relationship between rewards and performance, whereas mediation in the relationship between punishments and performance did not show the same significance. These findings emphasize the importance of implementing a fair and constructive reward system to enhance employee motivation and performance.